Comparisons of the technical, financial risk and life cycle assessments of various processing options of sugercane bagasse to biofuels in South Africa - Petersen, Abdul Muhaymin (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--Stellenbosch University, 2012